Coming Together While Staying Apart : Facilitating Collective Action through Trust and Social Connection in the Age of COVID-19 - Davenport, Stephen R. (World Bank, Washington, DC, 2020)
Facing the COVID-19 pandemic requires an unprecedented degree of cooperation between governments and citizens and across all facets of society to implement spatial distancing and other policy measures. This paper proposes to think about handling the pandemic as a collective action problem that can be alleviated by policies that foster trust and social connection. Policy and institutional recommendations are presented according to a three-layered pandemic response generally corresponding to short-, medium-, and long-term needs. This paper focuses on building connection and cooperation as means to bring about better health and socioeconomic outcomes. Many factors outside the paper’s scope, such as health policy choices, will greatly affect the outcomes. As such, the paper explores the role of trust, communication, and collaboration conditional on sound health and economic policy choices.